2021
DOI: 10.1111/wrr.12988
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the circ_PRKDC/miR‐20a‐3p/RASA1 axis in regulating HaCaT keratinocyte migration

Abstract: Migration of keratinocytes plays a crucial role in the re‐epithelialization phase during wound healing. Circular RNA (circRNA) protein kinase, DNA‐activated, catalytic subunit (circ_PRKDC, hsa_circ_0084443) has been identified as a regulator of keratinocyte migration. However, the molecular basis governing it remains unclear. The levels of circ_PRKDC, microRNA (miR)‐20a‐3p, and RAS p21 protein activator 1 (RASA1) were assessed by quantitative real‐time PCR (qRT‐PCR) or western blot. Subcellular localization, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…circRNAs have unique advantages in the development of disease diagnosis and treatment strategies due to their stronger stability, tissue and disease specificity. Recently, accumulating studies have found that circRNAs were closely related to skin wound healing 8,[32][33][34] . In this study, we found that the expression of circCDK13 was down-regulated in diabetic wounds, and then confirmed that circCDK13 could promote the proliferation and migration of HDFs and HEKs in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs have unique advantages in the development of disease diagnosis and treatment strategies due to their stronger stability, tissue and disease specificity. Recently, accumulating studies have found that circRNAs were closely related to skin wound healing 8,[32][33][34] . In this study, we found that the expression of circCDK13 was down-regulated in diabetic wounds, and then confirmed that circCDK13 could promote the proliferation and migration of HDFs and HEKs in vitro.…”
Section: Discussionmentioning
confidence: 99%